If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 7z + 6 Reorder the terms: 5 + 2x = 7z + 6 Reorder the terms: 5 + 2x = 6 + 7z Solving 5 + 2x = 6 + 7z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 6 + -5 + 7z Combine like terms: 5 + -5 = 0 0 + 2x = 6 + -5 + 7z 2x = 6 + -5 + 7z Combine like terms: 6 + -5 = 1 2x = 1 + 7z Divide each side by '2'. x = 0.5 + 3.5z Simplifying x = 0.5 + 3.5z
| (-3)(-4)+7= | | 20-6(2x-3)=-4 | | 3(x-10)=90 | | 4(x-5)-5=6x+7*4-4x | | Y=12.8+.6Y | | -7+y=-14 | | 5-y=14 | | 8c-72=12c-36-4c | | 4(w-6)=8 | | -7y+-2=-9 | | N+12=20-2n | | -4x-3y=15 | | 11-y=3 | | 12+n=20-2n | | 5(3+6x)-3(7-3x)= | | 4.2y=29.4 | | -44x+12y+4= | | -4.5=3x+1.5 | | -3+y=-4 | | 5y-9=2y+9 | | ln(x)+ln(x+6)=7 | | -4y=40 | | 2a^3-2a^2-84a=0 | | 5w-4=16-5w | | 6(x-9)-(x+12)= | | 4x-2(2x)=0 | | 3.2+0.8= | | 9-y=7 | | -2g(-6-4g)= | | -3m=0.923076 | | 2x-2(2x-8)=3(2x-7)+7x | | 10=6x-26 |